Centralization through decentralization? The crystallization of social order in the European Union. Issue 1 (1st January 2021) - Mueller, Sean; Hechter, Michael
ABSTRACT: Attaining social order is one of the principal dilemmas in the social sciences. Whereas most individuals and polities would be better off in a highly ordered society, their self-interested motivations instead often lead them to forgo cooperation and engage in behaviour that undermines social order. This paper develops a novel theory – termed crystallization – that shows how inter-territorial cooperation at lower levels of organization can sustain social order at a higher level. The framework is tested empirically to account for the integration of the European Union. All told, it is found that the extent of regional authority within a European Union member state is positively correlated with that state's legal and economic integration into the European Union. These results are compatible with a modified account of liberal intergovernmentalism. More generally, it is contended that large-scale cooperation between groups or states is causally linked to the concatenation of smaller scale governance units and polities nested within them. Thus, it emerges, somewhat paradoxically, that further centralization at the European Union level is likely to be encouraged by decentralization within the member states.